ON THE RADIATION SAFETY NORMS NRB-99/2009 AND BASIC SANITARY RULES OF RADIATION SAFETY OSPORB-99/2010 USE PROCEDURE DURING SUPERVISING AFTER THE HUMAN X-RAY SCANNERS - . Роспотребнадзор (Радиационная гигиена)
.